Head and Neck Swelling: A Cytopathological Perspective in a Hospital Based Study. - Shrestha, Sujan; Khadka, Dinesh; Bhandari, Sujita (Birat Journal of Health Sciences, 2021)
Introduction: Fine Needle Aspiration Cytology is a simple, relatively less painful, cost-effective minimal invasive procedure commonly employed in the evaluation of head and neck swellings. There are limited studies on cytological findings of head and neck swelling in Nepal.Objectives: The objective of this study was to study cytological findings of head and neck swellings. This study further intends to classify the nature of the swelling and use standardized international reporting system wherever required.Methodology: This is a retrospective hospital-based study done in the Department of Pathology at the Helping Hands Community Hospital, Kathmandu between 1 January 2019 and 32 December 2019. Slides of all FNAC from head and neck swelling done during this period was retrieved and evaluated for the study. Chi-Squared (χ2) test was used to investigate the significance of epidemiological and cytological parameters.Results: Males (56%) had more head and neck swelling than females (44%). The younger age group of less than twenty-five (< 25) years had more frequency of head and swelling followed by the older age group of more than fifty (>50) years. The most common site for Fine needle aspiration was lymph nodes (58%) followed by thyroid swelling (23%). Salivary gland swellings were the least frequent (5%). Of all the swelling, 17% of cases were attributed to malignant causes. Infective/Inflammatory causes (55%) were the most common cause of lymph node swellings. Metastatic carcinoma was more prevalent in the older age group of more than fifty (>50) years with a prevalence of 21% of total cases studies. Most of the thyroid swellings were found to be benign (58%) whereas 16% of thyroid swellings belonged to the malignant category. The total numbers of salivary gland swelling were the least with 55% of cases having benign neoplastic etiology. Diagnosis of developmental anomalies like a thyroglossal cyst, lymphangioma, branchial cyst, though relatively less common (10%) were also made with the help of cytologic studies.Conclusion: Fine Needle Aspiration is a useful method to differentiate benign and infective cases of head and neck swelling from neoplastic cases.